2017
DOI: 10.1371/journal.pone.0175342
|View full text |Cite
|
Sign up to set email alerts
|

Comparing two types of perspective taking as strategies for detecting distress amongst parents of children with cancer: A randomised trial

Abstract: ObjectiveTo compare two perspective taking strategies on (i) clinicians’ ability to accurately identify negative thoughts and feelings of parents of children with cancer, and (ii) clinician distress.MethodsSixty-three hematology-oncology professionals and nursing students watched a video featuring parents of children with cancer. Participants were randomly assigned to one of two groups. In the imagine-self group, they were instructed to imagine the feelings and life consequences which they would experience if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 55 publications
(68 reference statements)
1
10
0
2
Order By: Relevance
“…In the present study, parents were instructed to infer the experience of their child, that is, to take their perspective while completing analogous versions of the BYI and DRS. Additional instructions stated: “Answer each question the way you think your child has answered by taking the perspective of your child.” Previous research in oncology and other conditions has shown that such instructions prompted perspective‐taking responses on internalized symptoms . This was done in order to elicit a substitute judgment from the parent that mirrors the child's personal impression about their anxiety, depression, and distress.…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, parents were instructed to infer the experience of their child, that is, to take their perspective while completing analogous versions of the BYI and DRS. Additional instructions stated: “Answer each question the way you think your child has answered by taking the perspective of your child.” Previous research in oncology and other conditions has shown that such instructions prompted perspective‐taking responses on internalized symptoms . This was done in order to elicit a substitute judgment from the parent that mirrors the child's personal impression about their anxiety, depression, and distress.…”
Section: Methodssupporting
confidence: 91%
“…Previous research in oncology and other conditions has shown that such instructions prompted perspective-taking responses on internalized symptoms. [43][44][45][46] This was done in order to elicit a substitute judgment from the parent that mirrors the child's personal impression about their anxiety, depression, and distress. This was preferred here since anxiety, depression, and distress are internalized symptoms, the best source of information lies with the survivor's own experience.…”
Section: Parent Report Of Child Anxiety Depression and Distressmentioning
confidence: 99%
“…A recent study suggests that concentrating too highly on personal emotions is associated with decreased ability to detect distress in persons affected by cancer. 49 Future studies should explore more systematically the mechanisms underlying the effects of emotional competencies on PT. Participants did not improve on EC.…”
Section: Discussionmentioning
confidence: 99%
“…A child's oncological disease is a critical life event with the high burdening potential for most parents (Gouvela et al 2017). Each year in the United States of America, nearly 12,500 new oncological diseases are diagnosed among children and adolescents (National Cancer Institute 2013; Kazak and Noll 2015), which is the second-highest cause of death among children (Kazak and Noll 2015).…”
Section: Introductionmentioning
confidence: 99%